Addressing Governance Gaps in the Global Digital Ecosystem: The Role of Multilateral Collaboration and UNDP's Digital Strategy - Melati Nur Safitri (Asian Digital Governance Problems, 2025)
Purpose: This study aims to explore how multilateral collaboration, particularly through the United Nations Development Programme (UNDP) Digital Strategy 2022–2025, addresses the governance gap that continues to shape the global digital ecosystem. It seeks to understand how institutional cooperation, ethical frameworks, and strategic interventions converge to build inclusive and sustainable digital governance models across diverse national contexts. Subjects and Methods: The study employed a mixed methods approach using a convergent parallel design. Quantitative data were obtained from UNDP, ITU, World Bank, and EGDI databases, while qualitative data were collected through document analysis and semi-structured interviews involving 15 participants from international organizations, academia, government institutions, and civil society. Data were analyzed using descriptive statistical interpretation and thematic analysis. Results: The findings indicate that governance effectiveness, institutional readiness, and multilateral cooperation significantly influence digital governance capacity and public digital service accessibility. Persistent inequalities in digital infrastructure, institutional adaptation, and digital literacy continue to shape governance disparities, particularly in developing regions. Ethical governance frameworks emphasizing transparency, accountability, and participatory oversight were found to strengthen institutional legitimacy and public trust. Conclusions: Sustainable digital governance requires collaborative international engagement, adaptive institutional capacity, inclusive digital policies, and ethical governance mechanisms capable of balancing technological innovation with social equity and institutional accountability.